Antibacterial and sporicidal activity of Indonesian bay leaf (Eugenia polyantha Wight) extract against Bacillus cereus and Bacillus subtilis - Lau, Kah Yan (2015)
Spore-forming bacteria, Bacillus sp., have often been associated with the contamination of rice and other starchy products. Spores are more resistant to antimicrobial treatments than its vegetative cells. In this study, 26 methanolic plant extracts were screened for sporicidal activity against the spores of Bacillus cereus ATCC 33019. The extract of Indonesian bay leaf (Eugenia polyantha Wight), a spices used in Indonesian culinary, showed the most potential sporicidal activity against B. cereus ATCC 33019. E. polyantha extract was selected and further assessed for antibacterial and antispore activity. The Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) of E. polyantha extract against vegetative cells of B. cereus ATCC 33019, 25 of B. cereus isolated from various rice samples, B. subtilis ATCC 6633, B. subtilis KCTC 1028 and B. subtilis KCTC 3014 was determined as described by Clinical and Laboratory Standards Institute (CLSI) reference methods. The results showed that E. polyantha extract was able to inhibit the growth of vegetative cells of all tested Bacillus sp. with MICs ranged from 0.16 to 0.63 mg/mL. The extract can kill all the tested Bacillus sp. with MBCs ranged from 0.31 to 2.50 mg/mL. Time-kill curves were established for B. cereus ATCC 33019, B. cereus BC-NP.8, B. subtilis ATCC 6633 and B. subtilis KCTC 3014 at concentrations ranging from 0× MIC to 8× MIC at 30°C incubation. The bactericidal endpoint for B. cereus ATCC 33019 and B. subtilis KCTC 3014 were at concentration of 2.50 mg/mL (8× MIC), whereas B. cereus BC-NP.8 at 1.25 mg/mL (8× MIC) and B. subtilis ATCC 6633 at 5.00 mg/mL (8× MIC) after 4 h of incubation. The effect of different concentrations, incubation periods, pHs and temperatures on the sporicidal activity of E. polyantha extract was determined against spores of B. cereus ATCC 33019, B. cereus BC-NP.8, B. subtilis ATCC 6633 and B. subtilis KCTC 3014. Glutaraldehyde, a chemical sporicidal agent, was used as positive control. E. polyantha extract inactivated more than 3-log10 (99.99%) of B. cereus ATCC 33019, B. cereus BC-NP.8, B. subtilis ATCC 6633 and B. subtilis KCTC 3014 spores at a concentration of 1.0% after 1 h of incubation and the spores was completely killed at 2.5%. The sporicidal activity of E. polyantha extract was not affected by different temperatures treatment and alteration of the pHs of extract. These results indicate that the extract is stable against changes in pH 3, 7 and 10 as well as temperature of 50, 80 and 121°C. Based on scanning electron microscope observation, the structure of the B. cereus ATCC 33019 and B. subtilis ATCC 6633 spores was destroyed after treated with 1% (w/v) E. polyantha extract for 1 h. The LC50 of E. polyantha extract was found to be more than 1 mg/mL meaning that the extract is non-cytotoxic. Hexadecanoic acid, phytol and 9,12-octadecadienoic acid,(Z,Z), found in E. polyantha extract using GC-MS analysis as well as citral and eugenol found using LC-MS analysis might be contributing to the antibacterial and sporicidal activity. In summary, E. polyantha extract shows potential antibacterial and sporicidal activity against vegetative cells and spores of Bacillus sp.